Fuzzy Comprehensive Evaluation Method for Energy Management Systems Based on an Internet of Things - Yan Li; Zhiduo Sun; Liang Han; Ning Mei (IEEE Access, 2017)
An energy management system (EMS) that is augmented by Internet of Things (IoT) is introduced. Using IoT technology, real-time energy-consumption data can be efficiently collected and analyzed, leading to an improved awareness and evaluation of the energy consumption of manufacturing processes. The architecture and function of the IoT-based EMS are introduced. Because the existing monitoring standard for energy conservation defines only the minimum evaluation criterion, the result is either qualified or unqualified. Fully characterizing the energy consumption of industrial energy-intensive equipment is challenging. For this reason, this paper constructs a comprehensive evaluation model for monitoring industrial energy conservation. An evaluation index for industrial energy-intensive equipment is proposed. Then, by integrating an analytic hierarchy process and a fuzzy comprehensive evaluation method, a method is provided for an IoT-based industrial EMS to fully evaluate the operational level of energyintensive equipment. Finally, a case study is provided to verify the effectiveness of this method.